Sex differences in metabolic dysfunction-associated steatotic liver disease: a narrative review - Sae Kyung Joo; Won Kim (The Ewha Medical Journal)
Understanding the effects of sex and sex differences on liver health and disease is crucial for individualized healthcare and informed decision-making for patients with liver disease. The impact of sex on liver disease varies according to its etiology. Women have a lower prevalence of metabolic dysfunction-associated steatotic liver disease (MASLD) than men. However, postmenopausal women face a higher risk of advanced liver fibrosis due to hormonal influences. Sex differences affect the pathogenesis of MASLD, which involves a complex process involving several factors such as hormones, obesity, and the gut microbiome. Furthermore, sex-related differences in the development of MASLDrelated hepatocellular carcinoma have been observed. The sex-specific characteristics of MASLD necessitate an individualized management approach based on scientific evidence. However, research in this area has been lacking. This article reviews the current understanding of sex differences in MASLD.